DEVELOPMENT OF LEARNING MEDIA BIG BOOK MEDIA MATERIALS FOR OBJECTS FOR CLASS III STUDENTS OF SDN 030 TARAKAN - Hasmidah, Hasmidah; Mas'an Al Wahid, Sucahyo; Agustina, Degi Alrinda (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2024)
The learning problems at and 030 tarakan were that the learning process in the classroom looked more teeacher-cantered and there were someinactive students who felt bored, less focused, and needed to be faster to understand the material because teachers rarely used learning media. This study aimed to determine the feasibility of the media and the student’s response to the big book material. The deploment model used adopts the ADDIE theory. The steps of developing big book learning media are analysis, design, development, implementation, and evaluation. Experts conducted avalidation terst to determine the feasibility of the media. The resultsof the media validation test showed that the big book of object froms material scored 40 out of a maximum score of 50% with a Percentage of 90% (very feasible). in comparison, the material validation test scored 40 out of a maximum score of 50% with a percentage of 80% (feasible). the langueage validation test scored 40 out of a maximum score 50% with a persentage of 80% (feasible).with these results, it has met the requitrements and is suitable for use the results of students responses to the big book media during the limited trial whit a total of 5 studens obtained a score of 250 with a percentage of 100% (very interested). The results of the field trial with a total of 20 students scored 932 with a percentage of 93,2% (very interested). Based on the results of the validation of media experts, materials, language and student responses. the big book learning media on the material form of objects was expected to improve students understanding of learning material.